Banking Services Indices with Respect to Customer Satisfaction Vis-À-Vis Skills of Service Providers in Assam - DAS, DR. BIDYUT BIKASH (The journal of contemporary issues in business and government, 2021)
Many topics have been revealed and taught to us in the year 2020. We have seen economies collapse, unscrupulous attempts to take over businesses yet economies, and in the midst of all this chaos is the banking system, the core of a financial system and economies, the facilitator "transfer process," the trustee of the population for safekeeping their money, the advisor to the investor for making their money grow at an expected rate, and the guardian of the financial system and economies. Multiplicity of positions often leads to chaos, and the banker's job is to keep the consumer happy in the midst of it all. Customer, who is required to play the part of surplus unit saver and a key component of all economic operating cycles, leading to resource use and GDP. His happiness is the most important thing, and the banking system, as his protector, lawyer, and trustee, must provide it. As a result, core variables responsible for generating or enhancing this satisfaction must be established and handled in such a way that banking activities are not jeopardized and consumer satisfaction is maximized, ensuring stronger customer interest in the transition phase and allowing the economy to create more saving surplus units.